Transparent flexible thermoelectric material based on non-toxic earth-abundant p-type copper iodide thin film - C. Yang (Nature Portfolio, 2017)
Flexible thermoelectric devices with high optical transparency may enable new applications; however, the lack of a p-type counterpart has hitherto hindered its development. Yanget al., report a transparent p-type thermoelectric based on polycrystalline copper iodide thin film with record performance.